APPLICATION TEST OF EMPLOYEES PT.ARMORINDO OVER NEW PERSONALITY ARTHA USING MICROSOFT VISUAL BASIC 6.0 - Haritsyah Haritsyah; Cut Asiana Gemawaty, SKom., MMSI (Jurnal Sistem Informasi, 2006)
In scientific writing, the writer explains the data processing application programdesign test results into the prospective employee in PT. ARTHA ARMORINDOusing Microsoft Visual Basic 6.0. In this application program consists of 10 formsand use Microsoft Access for database.